Perbedaan Peran Komunikasi Keluarga dalam Penanaman Pesan Gizi Seimbang - Aurellya, Shafa; Ramadhana, Maulana Rezi (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The high number of toddlers experiencing stunting in Babakan Ciparay District has led the area to become a red zone for stunting cases in Bandung City. This is due to children's instant food consumption patterns, which overlook natural foods that tend to contain balanced nutrition. The role of family communication is needed to address stunting by conveying balanced nutrition messages. This study aims to understand the role of family communication, the application of socialization and education functions, and the differences in the role of family communication in conveying balanced nutrition messages between families with stunted children and families with normal-nourished children. The research method used is descriptive qualitative with a phenomenological approach and thematic analysis using ATLAS.ti software. The results of this study show that the role of family communication with stunted children is conceptualized based on high conversation and low conformity. The values of socialization and education functions applied by families with stunted children include self-confidence, creativity, responsibility, and cooperation. Furthermore, there are differences in the role of family communication in conveying balanced nutrition messages between families with stunted children and families with normal-nourished children in the application of socialization and education functions.